RE-ENACTING TRUMAN’S DOCTRINE BY NORTH ATLANTIC TREATY ORGANISATION (NATO) IN SUPPORT OF UKRAINE AMIDST RUSSIA’S ANNEXATION INTEREST - IWUOZOR, Pedro O.; ODOH, Samuel I.; Offor, E. Ogbonnaya (EBSU Journal of Social Sciences and Humanities, 2024)
The study sets out to analyse the application of Truman’s Doctrine by North Atlantic Treaty Organisation (NATO) in support of Ukraine in building economic and political stability amidst Russia’s subjugation and annexation interest. Scholars and international opinion leaders have averred that the ongoing Russia-Ukraine conflict gravely undermines Euro-Atlantic and global security, as Russia’s continued aggression towards Ukraine is a blatant violation of international law on the right to self-determination and sovereignty with its concomitant effects directly on Ukraine and on the global space. Essentially, the inability of scholars to scientifically address how NATO applies the Truman’s doctrine to promote economic and political stability of the Ukrainian state in the face of the ongoing Russia-Ukraine impasse constitutes the problematique of this study. The study adopted causal research design, also known as explanatory research; whereas, the beacon of analysis is hinged on the theory of responsibility to protect (R2P). The study deciphered that NATO has stood in unwavering solidarity with the government and people of Ukraine in the heroic defence of their nation, their land and their values to ensure stability in the polity amidst the conflict. NATO and its allies fully support Ukraine’s inherent right to self-defence as enshrined in Article 51 of the United Nations Charter. The study recommended that there is need for NATO to increase its supports to Ukraine in building economic and political stability, by bolstering Ukraine’s democratic institutions; invest in Ukrainian civil society organisations (CSOs); support independent media organisations and journalists in Ukraine; restore investors’ confidence; and support drivers of change in Russia and Belarus.